Identifikasi Senyawa Fitokimia Ekstrak Bulung Boni (Caulerpa sp.) dari Pantai Serangan - RAHMAWATI, DINA; WIRAWAN, I GEDE PUTU; SUDIARTA, I PUTU (Agrotrop : Journal on Agriculture Science, 2022)
Bulung boni ( Caulerpa sp.) is a type of algae that spreads in almost all Indonesian oceans. Generally, bulung boni grow in shallow water and attach to the sand substrate. This study aimed to determine the bioactive compounds of bulung boni and how they differ from other algae. The identification of bulung boni bioactive compounds was conducted using the GC-MS (Gas Chromatography-Mass Spectrometry) method. Based on the results of GC-MS analysis, bulung boni contains 10 compounds that mainly included into alkane group, i.e. 1-dodecene, Tetradecene, Decene, Pentadecene, Hexadecene, Dodecanol, Haxadecanoic acid, Heptadecene, Oktadecane, and Nanodecene.